PENDAMPINGAN PENYUSUNAN PELAPORAN KEUANGAN PADA KELOMPOK USAHA KECIL DAN MENENGAH BROSEM SEMERU - Gina Harventy; Siti Zubaidah; Masiyah Kholmi (Universitas Muhammadiyah Malang, 2020)
Financial statements are a means used by companies to communicate their activities and performance to stakeholders. Such is the case with UMKM Brosem. Financial reports are also prepared as a form of accountability of fund managers to